2020
DOI: 10.1016/j.kint.2020.01.039
|View full text |Cite
|
Sign up to set email alerts
|

The eye, the kidney, and cardiovascular disease: old concepts, better tools, and new horizons

Abstract: Chronic kidney disease (CKD) is common, with hypertension and diabetes mellitus acting as major risk factors for its development. Cardiovascular disease is the leading cause of death worldwide and the most frequent end point of CKD. There is an urgent need for more precise methods to identify patients at risk of CKD and cardiovascular disease. Alterations in microvascular structure and function contribute to the development of hypertension, diabetes, CKD, and their associated cardiovascular disease. Homology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 157 publications
2
65
0
2
Order By: Relevance
“…We report changes in the choriocapillaris microvasculature that is associated with kidney function (eGFR and urine MCR levels). The arrangement of the choriocapillaris and kidney glomerular microvasculature have several structural and organizational similarities that support the concept that choriocapillaris microvascular network might reflect changes in kidney microvasculature associated with renal disease 32 . We can therefore hypothesize that the presence of large CFD, signifying microvascular rarefaction, may mirror similar alterations in the renal microcirculation.…”
Section: Mechanisms Underlying Choriocapillaris Flow Deficits In Systsupporting
confidence: 59%
“…We report changes in the choriocapillaris microvasculature that is associated with kidney function (eGFR and urine MCR levels). The arrangement of the choriocapillaris and kidney glomerular microvasculature have several structural and organizational similarities that support the concept that choriocapillaris microvascular network might reflect changes in kidney microvasculature associated with renal disease 32 . We can therefore hypothesize that the presence of large CFD, signifying microvascular rarefaction, may mirror similar alterations in the renal microcirculation.…”
Section: Mechanisms Underlying Choriocapillaris Flow Deficits In Systsupporting
confidence: 59%
“…Examination of the microvasculature in this way has been used extensively in the research of both retinal and neurological disorders [ 17 , 18 ]. Moreover, retinal microvascular changes have been linked to increased cardiovascular risk [ 19 , 20 ], including the incidence of stroke [ 21 ] and coronary heart disease [ 22 ], suggesting that these abnormalities may reflect systemic microcirculatory dysfunction, and could represent an early, non-invasive technique to detect subclinical vascular pathology [ 22 ]. Cirrhosis is associated with widespread microcirculatory dysfunction and haemodynamic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The eye and kidney have several structural, developmental, and organizational similarities 6 ; current studies suggest that DN and DR share common microvascular pathophysiologic mechanisms, including inflammation, endothelial dysfunction, oxidative stress, and thickening of the basement membrane. 7 Several epidemiologic studies suggested DR and DN usually progress parallelly and share close relationship 8 ; thus, it is reasonable to assume that the severity of DR is a predictor of renal function.…”
Section: Introductionmentioning
confidence: 77%